1998
DOI: 10.1093/plankt/20.7.1357
|View full text |Cite
|
Sign up to set email alerts
|

The critical pressures of gas vesicles in Planktorhrix rubescens in relation tothe depth of winter mixing in Lake Zürich, Switzerland

Abstract: The vertical distribution of the cyanobacterium Planktothrir (Oscillazoria) rubescens in Lake Zürich was investigated from March 1993 to June 1995 by collecting filaments on filters and measuring them by epifluorescence microscopy and computer image analysis. The initial population, which began to stratify in April, decreased by up to 99% by June. During the summer, the population peaked at depths of 8-15 m; it reached a maximum areal filament-volume concentration of -60 cm −3 of lake surface in early Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 20 publications
7
101
0
Order By: Relevance
“…As in the two previous years (Walsby et al, 1998) the population of Planktothrix rubescens developed from a small remnant of the previous year's growth in the metalimnion (Fig. 3).…”
Section: The Population Of Planktothrix Rubescenssupporting
confidence: 52%
See 2 more Smart Citations
“…As in the two previous years (Walsby et al, 1998) the population of Planktothrix rubescens developed from a small remnant of the previous year's growth in the metalimnion (Fig. 3).…”
Section: The Population Of Planktothrix Rubescenssupporting
confidence: 52%
“…Thomas & Ma$ rki (1949) investigated the annual changes in the depth distribution of the population over 3 yr from January 1945 to December 1947 ; they showed that Planktothrix rubescens stratified in the metalimnion of Lake Zu$ rich during the summer, became entrained in the surface mixed layer during the autumn and was mixed to depths of 80 m or more during the winter. We showed a similar pattern during the period from March 1993 to June 1995, in which we measured the Planktothrix population by computer image analysis of filaments collected on membrane filters from samples taken at 10-20-m depth intervals each month (Walsby, Avery & Schanz, 1998). By integration of the filament concentration throughout depth in the water column, we demonstrated that the population fell to a minimum in May and June, reformed in the metalimnion, and grew throughout the summer to reach its maximum biomass in the autumn.…”
Section: mentioning
confidence: 62%
See 1 more Smart Citation
“…In Lake Bourget (Vinçon-Leite et al, 2002;Jacquet et al, 2014b;Anneville et al, 2015), as well as in other deep lakes like Lake Zurich (Walsby et al, 1998;Posch et al, 2012), Lake Garda (Salmaso, 2010) and Mondsee (Dokulil and Teubner, 2012), the abundance of P. rubescens by the end of winter is largely determined by meteorological conditions during winter. In such deep, warm monomictic lakes, cooling in mild winters may end up being insu cient to cause a full overturn, leading to a reduced dilution of the P. rubescens concentrations, as well more P. rubescens cells survive the winter (Walsby et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Gas vesicles of P. rubescens are known to collapse at high pressures (70-90 m in the strains found in Lake Zurich Walsby et al, 1998). In reality, this only a ects their buoyancy, and consecutively leads to an increased sedimentation of P. rubescens, but as we do not explicitly account for buoyancy in this study, we mimic this e ect by parameterizing the mortality rate of AP R as a sigmoidal function of depth, that has the in iction point at z=40 m, converging to l i=P R (=0.02 d −1 , as all other plankton, see Table3) at the surface, and 5*l i=P R (=0.1 d −1 ) towards 80 m:…”
Section: Biological Modelmentioning
confidence: 99%